On the effects of multifunctional agriculture on food security and viability of rural areas: review of current knowledge - Miettinen, Antti (Maatalouden taloudellinen tutkimuslaitos, 2000)
Agriculture produces multiple benefits and costs to societies. In most cases, a policy focusing on one particular benefit or cost influences also the supply of the others. This study is concerned with the contribution of agriculture to food security and rural welfare. Food security in Finland serves mainly as a precautionary measure against supply shocks by means of adequate domestic production and public security storage. The significance of agriculture in the rural areas is still substantial, even if the employment opportunities in agriculture have declined for a long time. Several other lines of business offer better prospects for future growth than agriculture. Therefore, it is important to pursue diversifying structural policy and promote also other sources of living than agriculture in the rural areas. To create and attain multiple benefits, rural policy should be directed to spatial development and nature conservancy.
Keywords: Ma; huoltovarmuus; monivaikutteisuus; maaseutualueiden hyvinvointi; food security; multifunctionality; rural welfare